How to live longer & healthier (Berkeley, 1966)
Examining life expectancy, this book suggests that it is possible to live for 120 years. It outlines the nutrients, pharmaceuticals, and techniques needed and how they can help us to live longer, as well as including information on everything from herbs to hormone replacement.
Keywords: Longevity,Tuổi thọ cao